PEMBUATAN TRIANGLE PANCAKE BERBAHAN DASAR UBI MADU CILEMBU - Safitri, Asifah Nur; Febriyanto, Fauzan; Ahsin, Karima Asyifa; Amarthani, Nur Tirta; Nur‘Aini, Syifa Hanum; Handayani, Langlang (Universitas Bunda Mulia, 2024)
Pancakes are a popular food and are often consumed throughout the world. To increase the variety and nutritional value of pancakes, this research aims to develop a recipe using honey sweet potato as the basic ingredient. Honey sweet potatoes were chosen because of their high nutritional content and as a substitute for flour with better carbohydrate content, namely the complex carbohydrate content found in sweet potatoes, as well as their natural sweet taste. This research method includes processing the ingredients, and the recipe used, and testing the resulting pancakes. The research results show that pancakes made from honey sweet potatoes have a soft texture and an attractive aroma. The test consists of testing the taste and texture of these pancakes. These findings show the potential for using honey sweet potato as an alternative basic ingredient in making healthy and nutritious pancakes.